The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1128/mbio.03372-22
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin Treatment Failure-Associated Mutation, Y1320H, in the RNA-Dependent RNA Polymerase of Genotype 3 Hepatitis E Virus (HEV) Enhances Virus Replication in a Rabbit HEV Infection Model

Abstract: HEV-3 causes chronic hepatitis E that requires antiviral therapy in immunosuppressed individuals. RBV is the main therapeutic option for chronic hepatitis E as an off-label use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…S6C ). Consistent with previous studies ( Debing et al., 2014 , 2016 ; Wang et al., 2023 ), two single mutants exhibit significantly higher ratios of HEV-positive cells compared with wild type (WT). In contrast, the double mutant strain does not exhibit enhanced levels of HEV, probably due to the incompatibility of these two mutations.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…S6C ). Consistent with previous studies ( Debing et al., 2014 , 2016 ; Wang et al., 2023 ), two single mutants exhibit significantly higher ratios of HEV-positive cells compared with wild type (WT). In contrast, the double mutant strain does not exhibit enhanced levels of HEV, probably due to the incompatibility of these two mutations.…”
Section: Resultssupporting
confidence: 91%
“…However, a proportion of patients either does not respond to treatment or remain viremic despite long-term ribavirin treatment ( Kamar et al., 2014 ). Moreover, ribavirin-associated mutations in HEV RNA polymerase may increase the replication capacity of HEV, thereby complicating the disease outcomes ( Debing et al., 2014 , 2016 ; Wang et al., 2023 ). Lastly, both PegIFN-α and ribavirin are contraindicated for use in pregnant women ( Kinast et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“… 37 Ribavirin treatment failure-associated mutation Y1320H in the RNA-dependent RNA polymerase of HEV gt 3 has been found to enhance virus replication in a rabbit HEV infection model. 38 The ability of ribavirin to induce HEV mutagenesis in treated patients has been reported. 37 The analysis of plasma HEV kinetic patterns in 41 SOT patients during ribavirin therapy demonstrated no association with response to therapy, with the exception of a flat-partial response.…”
Section: Hev In Solid Organ Transplant (Sot) Recipientsmentioning
confidence: 99%
“…It was also recently shown that although RBV increases viral heterogeneity, RBV-induced metagenesis seems to be reversible after therapy is stopped [ 82 ]. Another study showed that an RBV-failure-associated mutation (Y1320H) in the RNA-dependent RNA polymerase of HEV genotype 3 enhanced viral replication in a rabbit HEV infection model [ 83 ]. A more precise investigation is needed to clarify the effect and the reason for failure of the RBV treatment.…”
Section: Chronic Hepatitis E (Che)mentioning
confidence: 99%